Effectiveness of polypropylene mesh coated bovine amniotic membrane with adhesion barrier (polyethylene glycol) in repair of abdominal wall hernias in rats - Rashid, Hawar Qadir; Karabulut, Enis; Cevik, Aydin (Indian Counc Agricultural Res, 2018)
This study was undertaken to investigate the effectiveness of polypropylene (PP) mesh coated bovine amniotic membrane (BAM) with 5% polyethylene glycol (PEG) 4000 as adhesion barrier in the repair of experimental 2 x 2 cm of abdominal hernias in rats. Rats (32) were divided into 4 groups. A 2 cm x 2 cm defect was created in the full thickness of abdominal muscle on the anterior abdominal wall. PP mesh was implanted in the abdominal cavity (Gr 1 to 4). BAM covered the abdominal face of the graft (Gr 3 and 4). It was given before the abdominal closure 5 ml of 5% PEG 4000 (Gr 2 and 4) and 5 ml of 0.9% NaCl (Gr 1 and 3). After 21 days following the operations, 32 rats were euthanized. Macroscopic and microscopic evaluations were performed according to the scoring systems. The differences between the groups was evaluated by Mann-Whitney U test and Kruskal Wallis analysis of variance. Highest adhesion percentage was observed in Gr 1 and lowest in Gr 4. Inflammatory reaction was observed in Gr 1 and 2. According to the results of this study, the combined use of BAM and 5% PEG 4000 was helpful to prevent the complications of PP mesh.
Keywords: Adhesion; Amniotic membrane; Bovine; Hernia; Polyethylene glycol; Polypropylene mesh